THE EFFECTIVENESS OF THE STEAM-PROKSI MODEL ON LOGICAL, CREATIVE, AND INNOVATIVE THINKING SKILLS IN ELEMENTARY SCHOOL NATURAL AND SOCIAL SCIENCE LEARNING - Marzuqoh, Indah; Suriswo, Suriswo; Muljani, Sutji (Elementar : Jurnal Pendidikan Dasar, 2025)
Abstract This study aims to describe the implementation of the STEAM-PROKSI (Student Innovation Creativity and Synergy Project) model in IPAS Phase B learning and evaluate its impact on the development of logical, creative, and innovative thinking skills in elementary school students. The research approach used is a mixed method, which combines descriptive qualitative and quasi-experimental approaches. A qualitative approach was used to explore the learning process, student experience, and teacher and student perception of the application of the STEAM-PROKSI model, with a case study method carried out in two elementary schools in Moga District, Pemalang Regency. Qualitative data collection techniques include observation during the learning process, in-depth interviews with teachers and students, and documentation of student projects. Qualitative data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion/verification, with the validity of the data guaranteed through source and method triangulation techniques. Meanwhile, the quantitative approach uses a quasi-experimental design with two groups: the experimental group using the STEAM-PROXI model and the control group using the conventional approach. The instrument used was a high-level thinking skill test before and after treatment to measure the improvement of students' logical, creative, and innovative thinking skills. The results of the study show that the application of the STEAM-PROXSI model is able to create a meaningful and contextual learning experience, as well as encourage students to develop high-level thinking skills through project activities that are integrated with real life. Despite challenges in time planning, resource availability, and the implementation of a cross-disciplinary approach, overall the implementation of this model was considered effective. These findings recommend STEAM-PROKSI as an alternative innovative learning model in supporting the implementation of the Independent Curriculum, especially in science subjects at the elementary school level STEAM-PROKSI, IPAS, Thinking Skills, Elementary school